Aggiornamento and Dialogue: Some Ambiguity from Gaudium et Spes - Briola, Luke (Lumen et Vita, 2016)
At the heart of ecclesial mission, and thus of theology, is a diligent reading, discernment, and elevation of the signs of the times in the light of Jesus Christ. Such was the imperative of the Second Vatican Council’s Pastoral Constitution on the Church in the Modern World, Gaudium et spes, that has today been freshly received in the papacy of Francis. Precisely in order to attentively listen to those yearnings of the world, the word of the Council and arguably of Francis’s entire pontificate has been dialogue. Meanwhile, alongside excitement and hope, confusion and controversy continues to surround the legacy of the Council and the assessment of Pope Francis. The most recent Synod on the Family has demonstrated as much. This paper suggests that one of the issues-under-the-issues is the precise meaning of “dialogue,” an ambiguity that can be traced back to Gaudium et spes itself. After considering the positions of Joseph Ratzinger and Edward Schillebeeckx vis-à-vis Gaudium et spes, this paper suggests that, in actuality, two conceptions of dialogue are present in the church’s pastoral constitution. This conciliar ambiguity regarding the precise meaning of dialogue between church and world—whether a bold one-sided kerygmatic proclamation of the Gospel sine glossa or a more reciprocal two-sided mutual learning—is undoubtedly one source of confusion in any discussion of ecclesial mission today and thus merits our further attention. This paper briefly proposes that three fundamental theological questions offer some aid to resolve this key tension in Gaudium et spes: the role of eschatology in the church’s life; the relationship of nature and grace; and where, what, and who the church is. To continue to receive the Council’s teaching on dialogue is essential—the church’s missionary mandate from Christ depends on it.